Study Of Knowledge Management As An Enabler To Leadership In A Globalized Economy - Wan Ahmad, Wan Farid (2010)
The objective of the research is to establish the relationship between the availability of knowledge management as a tool to management and the application of knowledge management in the domain of leadership practice.